Lameness Affects Cow Feeding But Not Rumination Behavior as Characterized from Sensor Data - Thorup, Vivi M.; Nielsen, Birte L.; Robert, Pierre-Emmanuel; Giger-Reverdin, Sylvie; Konka, Jakub; Michie, Craig; Friggens, Nicolas C. (Frontiers in Veterinary Science, 2016)
Using automatic sensor data, this is the first study to characterize individual cow feeding and rumination behavior simultaneously as affected by lameness. A group of mixed-parity, lactating Holstein cows were loose-housed with free access to 24 cubicles and 12 automatic feed stations. Cows were milked 3 times/day. Fresh feed was delivered once daily. During 24 days with effectively 22 days of data, 13,908 feed station visits and 7,697 rumination events obtained from neck-mounted accelerometers on 16 cows were analyzed. During the same period, cows were locomotion scored on four occasions and categorized as lame (n = 9) or not lame (n = 7) throughout the study. Rumination time, number of rumination events, feeding time, feeding frequency, feeding rate, feed intake and milk yield were calculated per day, and coefficients of variation were used to estimate variation between and within cows. Based on daily sums, using each characteristic as response, the effects of lameness and stage of lactation were tested in a mixed model. With rumination time as response, each of the four feeding characteristics, milk yield and lameness were tested in a second mixed model. On a visit basis, effects of feeding duration, lameness and milk yield on feed intake were tested in a third mixed model. Overall, intra-individual variation was < 15% and inter-individual variation was up to 50%. Lameness introduced more inter-individual variation in feeding characteristics (26-50%) compared to non-lame cows (17-29%). Lameness decreased daily feeding time and daily feeding frequency, but increased daily feeding rate. Interestingly, lameness did not affect daily rumination behaviors, fresh matter intake or milk yield. On a visit basis, a high feeding rate was associated with a higher feed intake, a relationship that was exacerbated in the lame cows. In conclusion, cows can be characterized in particular by their feeding behavior, and lame cows differ from their non-lame pen-mates in terms of fewer feed station visits, faster eating, less time spent feeding, and more variable feeding behavior. Further, daily rumination time was slightly negatively associated with feeding rate, a relationship which calls for more research to quantify rumination efficiency relative to feeding rate.